Effects of Exercise on Tumor Physiology and Metabolism. Issue 2 (March 2015) - Pedersen, Line; Christensen, Jesper Frank; Hojman, Pernille
<x xml:space="preserve">Abstract</x> Abstract Exercise is a potent regulator of a range of physiological processes in most tissues. Solid epidemiological data show that exercise training can reduce disease risk and mortality for several cancer diagnoses, suggesting that exercise training may directly regulate tumor physiology and metabolism. Here, we review the body of literature describing exercise intervention studies performed in rodent tumor models and elaborate on potential mechanistic effects of exercise on tumor physiology. Exercise has been shown to reduce tumor incidence, tumor multiplicity, and tumor growth across numerous different transplantable, chemically induced or genetic tumor models. We propose 4 emerging mechanistic effects of exercise, including (1) vascularization and blood perfusion, (2) immune function, (3) tumor metabolism, and (4) muscle-to-cancer cross-talk, and discuss these in details. In conclusion, exercise training has the potential to be a beneficial and integrated component of cancer management, but has yet to fully elucidate its potential. Understanding the mechanistic effects of exercise on tumor physiology is warranted. Insight into these mechanistic effects is emerging, but experimental intervention studies are still needed to verify the cause-effect relationship between these mechanisms and the control of tumor growth.